Keefektifan Konseling Mindfulness terhadap Penurunan Tingkat Stres Akademik pada Siswa SMP Negeri 24 Banjarmasin: The Effectiveness of Mindfulness Counseling in Reducing Academic Stress Levels in Students of SMP Negeri 24 Banjarmasin - Nur Abidah Az Zahro; Nina Permata Sari; Eklys Cheseda Makaria (ITScience (Information Technology and Science), 2025)
Academic stress is a common problem experienced by junior high school (SMP) students due to the increasing demands of learning and the dynamics of early adolescent development. If not managed adaptively, academic stress can reduce students' learning motivation and psychological well-being. This study aims to test the effectiveness of mindfulness-based group counseling, delivered through a mindfulness group counseling guidebook, in reducing academic stress among junior high school students. The study used a quantitative approach with a pre-experimental intact-group comparison design. The study subjects were 12 eighth-grade students of SMP Negeri 24 Banjarmasin who were in the high academic stress category and were divided into an experimental group and a control group. The research instrument was an academic stress questionnaire that had undergone validity and reliability testing, with a Cronbach's Alpha of 0.889. The intervention was delivered through four group counseling sessions using breathing-in and breathing-out techniques, the 'know your emotion' exercise, body-scan meditation, and 'thank you'. Data analysis used an independent samples t-test. The results showed a significant difference between the experimental and control groups (p < 0.05), with the experimental group showing a greater reduction in academic stress. These findings indicate that mindfulness-based group counseling is effective in reducing academic stress in junior high school students and has the potential to be developed as a preventive and responsive intervention in guidance and counseling services in schools.